2018
DOI: 10.14742/ajet.3836
|View full text |Cite
|
Sign up to set email alerts
|

Learning analytics experience among academics in Australia and Malaysia: A comparison

Abstract: Several studies have been conducted to evaluate the experience and involvement of academics in learning analytics (LA) due to its potential for improving teaching and learning. However, findings often reflect an educational culture which is indicative of the institutional or national context where the study has occurred, resulting in bias regarding LA perspectives. Therefore, this study seeks to compare and contrast the experiences of LA among academics in Australia and Malaysia, with intentions to learn from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 16 publications
0
31
0
1
Order By: Relevance
“…The studies presenting mixed locations conducted comparative studies. One study addressed universities in the UK, South Africa, and the United States (Willis, Slade, & Prinsloo, 2016), one collected and analyzed data from both the UK and the United States (Arnold & Sclater, 2017), and another compared responses from Australian and Malaysian universities (West et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies presenting mixed locations conducted comparative studies. One study addressed universities in the UK, South Africa, and the United States (Willis, Slade, & Prinsloo, 2016), one collected and analyzed data from both the UK and the United States (Arnold & Sclater, 2017), and another compared responses from Australian and Malaysian universities (West et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies do not explicitly report on the data analysis methods applied, although they clearly state the methodological approaches underpinning their studies (Lawson et al, 2016;Scott & Nichols, 2017). Among the works applying statistical methods, we observe the use of the statistical package for social analysis (e.g., Ifenthaler & Schumacher, 2016;West et al, 2016;Adejo & Connolly, 2017;Mahroeian et al, 2017), including descriptive (e.g., Arnold & Sclater, 2017), inferential statistics (e.g., Slade et al, 2019), exploratory and confirmatory factor analysis (e.g., Whitelock-Wainwright et al, 2019), as well as Rasch analysis (e.g., West et al, 2018). In the works using open coding, we distinguish open and axial descriptive coding (West et al, 2016(West et al, , 2018Brooker et al, 2017;Klein et al, 2019;Jones, 2019aJones, , 2019bTsai et al, 2019).…”
Section: Data Analysis Methods Reportedmentioning
confidence: 95%
See 2 more Smart Citations
“…Problems with teacher participation in LA was identified in a study by West et al (2016), who found that while teaching staff generally expressed a high level of interest in LA, their participation in LA activities and training was limited. A more recent study by West et al (2018) also found that using LA is not yet widespread and, as such, it is mostly done in isolation. The authors suggest that while such introspection may be influenced by a lack of LA adoption or the early stage of maturity of LA applications, it means that academics who are interested in LA often pursue their research in isolation and with no clear scope of how LA may be used to drive change.…”
Section: Adoption Of Learning Analytics In Higher Educationmentioning
confidence: 99%